Cytomegalovirus Uveitis with Hypopyon Mimicking Bacterial Endophthalmitis - Atsushi Yoshida; Hiroto Obata; Hidetoshi Kawashima (Case Reports in Ophthalmological Medicine)
We report an 83-year-old immune-competent female with unilateral endophthalmitis extraordinarily caused by cytomegalovirus (CMV). Since she was suspected of suffering possible bacterial endophthalmitis, she was referred to our hospital. At the first visit, hypopyon in the anterior chamber and the opacity of vitreous body were observed in the left eye. The best-corrected visual acuity (BCVA) of the left eye was counting fingers and the intraocular pressure (IOP) was 20 mmHg. Bacterial and fungus culture of the aqueous humor revealed no infection. However, the density of corneal endothelial cell was less than the measurable range and CMV was detected by PCR of the aqueous humor. She was immune-competent and the data indicated neither systemic infections nor diseases. Systemic valganciclovir and corticosteroid were administered. After that, hypopyon in the anterior chamber and the opacity of vitreous body of the left eye were improved, and the BCVA of the left eye was 20/200 one year after the first visit. However, the inflammation of the anterior chamber recurred accompanied by elevated IOP after the discontinuance of administering valganciclovir. CMV-induced uveitis accompanied with hypopyon is quite rare. Therefore, it can be easily misdiagnosed as bacterial endophthalmitis.